MANAJEMEN KOMUNIKASI PELAYANAN PUBLIK KLINIK HALIM FERTILITY CENTER MEDAN DALAM MENJAGA RIWAYAT PASIEN INFERTILITAS - Juhra, Muhammad Anshar; Pohan, Syafruddin (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
Maintaining patient history is a very important aspect in managing health information. Collecting and managing patient history data is also part of a health information system. Halim Fertility Center Medan Clinic is one of the clinics that provides fertility and IVF programs on the island of Sumatra. This clinic is a target for people experiencing infertility. This problem of infertility is a secret for married couples, so maintaining the history of infertility patients is the obligation of health managers. Public service communication management must be implemented well so that patient history remains accurate and useful in treatment. The aim of this research is to analyze how public service communication management is used by the Halim Fertility Center Medan Clinic in maintaining the history of infertility patients. This research uses qualitative research. Data collection used was in the form of interviews with medical officers at the Halim Fertility Center Medan Clinic. The results of this research show that the Halim Fertility Center Medan Clinic uses the Health Information System (SIK) manually without using an application. The patient history results are physically printed and stored in the patient history folder warehouse. The public service communication management flow at the Halim Fertility Center Clinic is also well designed and systematic, with medical personnel who work and are responsible according to their respective duties and functions. The obstacles found in maintaining the history of infertility patients at the Halim Fertility Center Clinic are technical obstacles, this is due to the manual use of the Health Information System (SIK).